A política na religião ou a religião na política?: considerações sobre representação religiosa na Legislatura 2.017-2.020 da Câmara Municipal de Belo Horizonte - Daniel Antonio da Cunha (2018)
This thesis examines the tensions involved in present democracy between the political, the religious and the juridical spheres. For this, it speaks of religious representations in Belo Horizontes City Council, in the 2017-2020 legislature, through ground research and bibliographical analysis. The field diary is composed of semi-structured interviews applied to elected councilors in the city of Belo Horizonte. In addition to the analysis of the interviews, the material and immaterial symbols of religion and politics observed in the CMBH environment are also glimpsed and highlighted as milestones of the constitutive tensions of this relation. It also analyzes the ground research results taking into account social indicators such as the Brazilian Institute of Geography and Statistics (IBGE) Census, and the 2.017 Research Perceptions and Political Values of the Perseus Abramo Foundation (FPA). In the scope of the bibliographical research, we sought to rescue the academic debate in the legal area and to aggregate the discussions on modernity, secularization and secularity of other disciplinary approaches in the areas of social sciences, especially those of the sociology of religion, as a contribution to the Law. Among the authors studied are, in Philosophy, Jürgen Habermas, and in Sociology, Max Weber, Faustino Teixeira and José Casanova. The draft laws and discussions on them during the period that precedes the previous legislature, starting in 2.017, and the main articulations for the approval of these projects in the current legislature were also investigated. In the end, the reader is expected to understand that the paradox of religion in politics, which is seen as a risk to a secular State, is concomitant to the least observed paradox of politics in religion. From the perspective of this double paradox it is possible to perceive why there are no ready and finished exits for the struggles against the fundamentalisms that threaten the Democratic Rule of Law. This challenge, if viewed from the perspective of consolidating democracy and pluralism, demands from us the ability to see the disputes that define the meanings of rights and open the margins of what is juridical.